Analysis effect of shade level on the physiological and anatomical characteristics of hybrid Phalaenopsis orchid at the acclimatization stage - Ade Arisma Fauziah; Nintya Setiari; Endang Saptiningsih (Kultivasi, 2022)
AbstractProduction of hybrid Phalaenopsis seedlings is generally applied by in vitro culture techniques. The final stage of in vitro culture is acclimatization. The acclimatization stage is crucial because the plantlets must adapt to the ex-vitro environment. Shade supports plantlet growth during the early stages of acclimatization. This study aims to determine the effect of shade level on the physiological and anatomical characteristics of the Phalaenopsis hybrid orchid at the acclimatization stage. The research used Phalaenopsis plantlet hybrid and shading level. Plantlets were shaded at 40%, 55%, and 70%. Parameters measured included: photosynthetic pigment content, number and area of leaves, number and length of roots, stomata density, size of stomata and fresh weight. This study used a completely randomized design with one factor and ten replications. Data were analyzed using the ANOVA test and LSD test at a significance level of 5% (p<0.05). The results showed the highest photosynthetic pigment content in the 55% shade, and there was a difference in the size of the stomatal guard cells between ex vitro and in vitro leaves at 40% shade. Shade level did not affect leaf growth, roots, fresh weight and stomata density. However, it affected photosynthetic pigment content and size of guard cells in the ex vitro leaves of Phalaenopsis hybrid orchids. The most optimal growth of the Phalaenopsis hybrid was at 55% shade.Keywords: acclimatization, ex vitro leaves, shade AbstrakProduksi bibit Phalaenopsis hibrid umumnya dilakukan dengan teknik kultur in vitro. Tahap akhir dari kultur in vitro adalah aklimatisasi. Aklimatisasi merupakan tahap paling penting karena planlet harus beradaptasi di lingkungan ex vitro. Naungan menunjang pertumbuhan planlet selama tahap awal aklimatisasi. Penelitian ini bertujuan untuk mengetahui pengaruh tingkat naungan terhadap karakteristik fisiologis dan anatomis anggrek Phalaenopsis hibrid pada tahap aklimatisasi. Penelitian menggunakan planlet Phalaenopsis hibrid dan tingkat naungan. Planlet diberi paranet 40%, 55%, dan 70%. Parameter yang diukur meliputi: kandungan pigmen fotosintesis, jumlah dan luas daun, jumlah dan panjang akar, densitas stomata, ukuran stomata dan berat segar. Penelitian ini menggunakan rancangan acak lengkap dengan satu faktor dan 10 ulangan. Data dianalisis menggunakan Uji ANOVA dan Uji LSD pada taraf signifikasi 5% (p< 0,05). Hasil penelitian menunjukkan bahwa kandungan pigmen fotosintesis tertinggi terdapat pada naungan 55% danterdapat perbedaan ukuran sel penutup stomata antara daun ex vitro dan in vitro pada naungan 40%. Tingkat naungan tidak mempengaruhi pertumbuhan daun, akar, berat segar serta densitas stomata, namun mempengaruhi kandungan pigmen fotosintesis serta ukuran sel penutup stomata daun ex vitro pada anggrek Phalaenopsis hibrid. Pertumbuhan Phalaenopsis hibrid yang paling optimal berada pada naungan 55%. Kata Kunci: aklimatisasi, daun ex vitro, naungan